A Examining Fuzzy Partial Metric Space and Associated Outcomes: Fuzzy Partial Metric Space and Associated Outcomes - Rohini Gore,; Renu Pathak, (Communications in Mathematics and Applications, 2025)
Using the concept of a PM space with fuzzy, we present idea of a FPMS in this paper. A point's self-distance in partial metric space does not always equal to zero. Ordinary metric is a subset of partial metric. Additionally, we define continuous t-Norms. Partial fuzzy contraction mapping is defined here. We also demonstrate that, in certain circumstances, the complete partial metric space has a common fixed point through use of contraction mapping. Relevant examples are used as provide results. 2020 AMS Classification: 47H10, 37C25, 30L15.